Stability Indicating HPLC Method for Simultaneous Quantification of Trihexyphenidyl Hydrochloride, Trifluoperazine Hydrochloride and Chlorpromazine Hydrochloride from Tablet Formulation - P. Shetti; A. Venkatachalam (E-Journal of Chemistry)
A new, simple, precise, rapid, selective and stability indicating reversed-phase high performance liquid chromatographic (HPLC) method has been developed and validated for simultaneous quantification of trihexyphenidyl hydrochloride, trifluoperazine hydrochloride and chlorpromazine hydrochloride from combined tablet formulation. The method is based on reverse-phase using C-18 (250×4.6) mm, 5 μm particle size column. The separation is achieved using isocratic elution by methanol and ammonium acetate buffer (1% w/v, pH 6.5) in the ratio of 85:15 v/v, pumped at flow rate 1.0 mL/min and UV detection at 215 nm. The column is maintained at 30 °C through out the analysis. This method gives baseline resolution. The total run time is 15 min. Stability indicating capability is established buy forced degradation experiment. The method is validated for specificity, accuracy, precision and linearity as per International conference of harmonisation (ICH). The method is accurate and linear for quantification of trihexyphenidyl hydrochloride, trifluoperazine hydrochloride and Chlorpromazine hydrochloride between 5 - 15 μg/mL, 12.5- 37.5 μg/mL and 62.5 - 187.5 μg/mL respectively.